Il dibattito su memoria e modernità nella museografia italiana del secondo dopoguerra: spazi espositivi tra idealismo e fenomenologia - Baldriga, Irene (Opus Incertum, 2023)
After World War II, the diffusion of Phenomenology was pivotal in inspiring a different consideration of the relationship between visitors and artworks, fostering Italian museological experimentation and the evolution of aesthetic thought. In this sense, the contributions of some art historians interested in promoting awareness and participation in museum experience were fundamental. By adopting a new perspective, the contribution analyzes some aspects of this cultural context, focusing in particular on the experience of Cesare Brandi and Carlo Ludovico Ragghianti.